Successful retrieval of a Figulla Occlutech septal occluder - embolized device stability and potential solutions - Masood Sadiq; Asif Ur Rehman; Amjad Mehmood (Wolters Kluwer Medknow Publications, 2016)
Go to: We report a case of an atrial septal defect where a Figulla Occlutech device embolized into the right ventricle. As this device has no left atrial hub, we brought the bare device into the inferior vena cava and used a novel two-snare technique to slenderize the device into the sheath. This report highlights additional tips in transcatheter device retrieval.